Branch library location in the southern suburbs of Cape Town: a study of the influence of certain distance on the operation and location of five branch libraries in the southern suburbs of Cape Town - Thorne, Athol Edwin (School of Architecture, Planning and Geomatics, 2021)
Rapidly rising cultural levels give the Public Library, as an institution, public services. a social significance comparable with most other Strongly linked on the one hand with vital educational institutions but providing also for the recreational needs of increasing millions of people on the other public library services are now claiming the attention not only of those closely concerned, such as professional librarians and city administrators, but also of a growing spectrum of social scientists, planners and urbanists. The importance of a widespread and efficient library system to a relatively advanced and progressive urban centre such as Cape Town therefore needs little emphasis.